British Consular Reports on Filipino Anti-Colonial Struggles and Philippine-British Relations, 1896-1902 - Pagunsan, Ruel (Philippine Social Sciences Review; Vol 62 No 1: January-June 2010, Ed. Eric Manalastas, 2011)
At the turn of the nineteenth century, British consular officials regularly reported to the Foreign Office in London the political occurrences in the Philippines. The United Kingdom’s huge economic investments in the Philippines prompted London to closely monitor the outcomes of the events. On the other hand, the Filipinos, particularly the government of Emilio Aguinaldo, capitalized on such economic interests by getting British support to the Filipino war for independence. This paper presents the accounts and insights of the British consuls on the two significant historical events that shaped Filipino nationhood—the Philippine Revolution and the Filipino-American War. The consular reports provide perspectives of the events different from the views of the colonialists and the Filipinos. Theirs actually was from a standpoint of a non-participant. Furthermore, this study also examines the United Kingdom’s policy and actions throughout the Filipino anti-colonial struggles, as well as the Philippine Revolutionary Government’s engagement with the British. Ultimately, this work hopes to contribute to the study of the country’s diplomatic history, particularly on Philippine-British relations.